Factors affecting the blockchain operation in Asia-Europe - Miraz, Mahadi Hasan; Jin, Hwang Ha; Hasan, Mohammad Tariq; Hossain, Mohammad Amzad; Hoque, Md Kazimul (International Journal of Management and Sustainability, 2024)
This study’s primary goal is to identify the factors that affect the blockchain in retail markets to support more significant benefits to retail customers. Also, this study constructs blockchain facilities, blockchain volatility, blockchain transactions, blockchain intentions, and blockchain operations. This research also used a questionnaire survey; this research collects primary data from consumers in Asia and Europe. The researcher also presents the underlying theory, the theoretical structure, and the hypotheses through systematic random sampling to ensure the research objectives. Besides that, there were 233 responses to the survey questions sent to retail consumers. PLS-SEM tools are used for data analysis. The study’s findings are that the Blockchain facility, blockchain volatility, and blockchain transaction were all found to positively impact the blockchain operation (dependent variable) in the Asia-Europe retail market via the mediation of behavior intention. The outcome of this research offers a valuable understanding of blockchain adoption in developing and developed countries. In addition to academic contributions, this paper’s findings are significant for blockchain companies and their operations in developing countries. Additionally, blockchain is beneficial to the Asia-Europe retail market. Hence, this study offers a considerable foundation for comprehending the associations between blockchain and the retail industry. This study did not consider SMEs or general industries. Also, this study’s scope is limited to Asia and Europe. Additionally, this study solely employed cross-sectional data. Future studies should use longitudinal data to better understand how the link develops.